Economical implications and the impact of gonadotropin-releasing hormone administration at the time of artificial insemination in cows raised in the extensive system in North Romania - Berean, Daniel; Bogdan, Liviu Marian; Opris, Petrică; Cimpean, Raluca (Frontiers in Veterinary Science, 2023)
Artificial insemination (AI) is the first and the most used Biotechnologies in Reproduction in all the world. Many studies reported the benefic role of GnRH administrated some hours before the AI or at the artificial insemination time. This study aimed to assess the effect of GnRH analogs given at the time of insemination on the first, second, and third AI and the economical implications of GnRH administration. We hypothesized that administration of GnRH at the time of insemination would increase ovulation and pregnancy rate. The study was conducted on small farms in northwestern Romania and included animals of the Romanian Brown and Romanian Spotted breeds. Animals in oestrus at the first, second, and third insemination were randomly divided into groups that received GnRH at insemination and groups that did not. A comparison between the groups was performed and the cost of GnRH administration to obtain 1 gestation was established. The GnRh administration increased the pregnancy rate at the first and at the second insemination by 12% respectively 18%. For one pregnancy, the cost of GnRH administration was approximately 49 euros for the first insemination group and around 33 euros for the second insemination group. No improvement of the pregnancy rate was observed after the GnRH administration for the cows at the third insemination, so, for this group were not performed economic stats.